Polyarylene sulfide composition with improved crystallization properties

CN122996129APending Publication Date: 2026-10-27TICONA LLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202580021347.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-01-27
Filing Date
2025-07-07
Publication Date
2026-10-27

Smart Images

  • Figure CN122996129A_ABST
    Figure CN122996129A_ABST
Patent Text Reader

Abstract

A polymer composition comprising 100 parts by weight of a polymeric matrix containing polyarylene sulfide and about 30 parts by weight to about 120 parts by weight of inorganic fibers. The polymer composition exhibits a peak crystallization temperature (T p,c ) of about 230 °C or greater and a tensile elongation of about 1.8% or greater.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Related applications

[0002] This application is based on and claims priority to U.S. Patent Application Serial No. 19 / 037,349, filed January 27, 2025, which is incorporated herein by reference. Background Technology

[0003] Polyphenylene sulfide (“PPS”) is a high-performance polymer capable of withstanding high thermal, chemical, and mechanical stresses. However, injection-molded parts from PPS can be challenging due to its relatively slow crystallization rate. For example, to achieve the desired crystallinity, molding is typically performed at high mold temperatures (around 130°C or higher) and relatively long cycle times. Unfortunately, high mold temperatures typically necessitate the use of expensive and corrosive cooling media (e.g., oil). Attempts to address these issues generally involve adding various additives to the polymer composition to help improve its crystallinity. However, such attempts have not been entirely satisfactory to date. In fact, these problems have become more pronounced as various industries (e.g., electronics, automotive, etc.) now require injection-molded parts with very small dimensional tolerances. In these applications, the polymer must possess good flow properties so that it can quickly and uniformly fill the small spaces of the mold cavity. However, it has been found that conventional PPS, which manages to meet the required high flowability, tends to result in significant “flash” (excess polymer material being extruded from the mold cavity at the junction of the two mold surfaces) during molding, especially with high temperatures and long cycle times. Excessive flash can affect product quality and necessitate costly and time-consuming trimming steps. Therefore, there remains a demand for polyarylene sulfide compositions that can be more easily injection molded into parts of various shapes and sizes. Summary of the Invention

[0004] According to one embodiment of the present invention, a polymer composition is disclosed comprising 100 parts by weight of a polymer matrix containing polyarylene sulfides and about 30 to about 120 parts by weight of inorganic fibers. The polymer composition exhibits a peak crystallization temperature (Tc) of about 230°C or higher, as determined by differential scanning calorimetry according to ISO 11357-3:2018. p,c (and approximately 1.8% or higher tensile elongation as determined at 23°C according to ISO 527:2019).

[0005] Other features and aspects of the invention will be set forth in detail below. Attached Figure Description

[0006] The complete and practicable disclosure of the present invention, including its best mode of practice for those skilled in the art, will be set forth in more detail in the remainder of the specification, including with reference to the accompanying drawings, in which:

[0007] Figure 1 An embodiment of an apparatus for injection molding the polymer composition of the present invention into a molded part is illustrated. Detailed Implementation

[0008] Those skilled in the art will understand that this discussion is merely a description of exemplary embodiments and is not intended to limit the broader aspects of the invention.

[0009] Generally, this invention relates to a polymer composition containing a polyarylene sulfide and a nucleation system comprising inorganic fibers. While the exact mechanism is not fully understood, the inventors have discovered that by selectively controlling the specific type and concentration of the inorganic fibers, the resulting composition can achieve excellent crystallization properties (e.g., crystallization rate). In this respect, the improved crystallization rate can be achieved by using a high peak crystallization temperature (Tc). p,c The temperature is characterized, for example, about 230°C or higher, in some embodiments about 232°C to about 270°C, and in some embodiments about 235°C to about 260°C, as determined by differential scanning calorimetry according to ISO 11357-3:2018. Due to the improved crystallization rate, the polymer composition can be molded at lower temperatures while still achieving the same degree of crystallinity. In addition to minimizing the energy requirements of the molding operation, using lower temperatures also reduces the generation of “flash” typically associated with high-temperature molding operations. For example, the length of any flash (also called burr) produced during the molding operation can be about 0.17 mm or less, in some embodiments about 0.14 mm or less, and in some embodiments about 0.13 mm or less.

[0010] It is noteworthy that it has been found that such improved crystallinity properties can be achieved without the use of conventional nucleating agents, such as boron nucleating agents (e.g., boron nitride, boron sulfide, boron chloride, boric acid, boron carbide, boron oxide, zinc borate, etc.). While it is generally desirable to minimize the presence of such conventional nucleating agents (e.g., boron compounds), they may still be present in relatively small percentages in some embodiments, for example, in amounts of about 0.5 wt.% or less of the polymer composition, about 0.1 wt.% or less in some embodiments, and about 0.001 wt.% to about 0.05 wt.% in some embodiments.

[0011] While exhibiting good crystallinity, the polymer composition still achieves relatively high strength and stiffness. For example, the composition can exhibit a tensile fracture strain (“elongation”) of about 1.8% or greater, in some embodiments about 2% to about 5%, and in some embodiments about 2.2% to about 4% (as determined according to ISO 527:2019 at a temperature of 23°C). The composition can also exhibit a tensile modulus of about 16,000 MPa or higher, in some embodiments about 17,000 MPa to about 35,000 MPa, and in some embodiments about 18,000 MPa to about 30,000 MPa (as determined according to ISO 527:2019 at a temperature of 23°C) and / or a tensile fracture stress (“tensile strength”) of about 100 MPa or higher, in some embodiments about 150 MPa to about 350 MPa, and in some embodiments about 180 MPa to about 300 MPa (as determined according to ISO 527:2019 at a temperature of 23°C). The composition may also exhibit a flexural modulus of about 10,000 MPa or higher, in some embodiments about 12,000 MPa to about 32,000 MPa, and in some embodiments about 14,000 MPa to about 30,000 MPa; and / or a flexural strength of about 100 MPa or higher, in some embodiments about 150 MPa to about 500 MPa, and in some embodiments about 225 MPa to about 450 MPa (as determined according to ISO 178:2019 at a temperature of 23°C). The polymer composition may exhibit high impact strength, for example about 5 kJ / m². 2 Or higher notched impact strength for simply supported beams, for example, about 6 kJ / m in some implementations. 2 Approximately 30 kJ / m 2 And in some implementations, it is approximately 7 kJ / m 2 Approximately 20 kJ / m 2 As determined according to ISO 179-1:2010 at a temperature of 23°C.

[0012] Furthermore, the polymer composition exhibits good flow properties, reflected in relatively low melt viscosity, for example, about 5,000 poise or less, about 4,750 poise or less in some embodiments, and about 500 poise to about 4,500 poise in some embodiments, as per ISO 11443:2021 at a temperature of about 310°C and 1,200 s. -1The shear rate was measured. The polymer composition can also be thermally conductive. For example, the composition can exhibit an in-plane (or "in the flow direction") thermal conductivity of about 2 W / mK or higher, about 0.1 W / mK or higher in some embodiments, about 0.15 W / mK to about 8 W / mK in some embodiments, and about 0.2 W / mK to about 6 W / mK in some embodiments, as measured according to ASTM E 1461-13. Similarly, the polymer composition can exhibit an out-of-plane thermal conductivity of about 0.4 W / mK or higher, about 0.5 W / mK or higher in some embodiments, and about 0.6 W / mK to about 4 W / mK in some embodiments, as measured according to ASTM E 1461-13. Such high thermal conductivity values ​​enable the composition to form thermal pathways for transferring heat away from electrical components employing the composition. In this way, "hot spots" can be quickly eliminated during use and the overall temperature can be reduced. Furthermore, the surface resistivity of the polymer composition can be about 5 × 10⁻⁶. 16 Ohms or less, in some implementations approximately 1 × 10⁻⁶ 16 Ohms or less, in some implementations approximately 5 × 10⁻⁶ 15 Ohms or less, and in some implementations approximately 1 × 10⁻⁶. 13 To approximately 1×10 15 Ohms, for example, are measured at a temperature of about 20°C according to IEC 62631-3-2:2016.

[0013] The various embodiments of the present invention will be described in more detail below.

[0014] I. polymer composition

[0015] A. polymer matrix

[0016] The polymer matrix typically constitutes about 40 wt.% to about 90 wt.% of the polymer composition, about 45 wt.% to about 85 wt.% in some embodiments, and about 50 wt.% to about 80 wt.% in some embodiments. The polymer matrix contains at least one polyarylene sulfide. For example, the polyarylene sulfide typically constitutes about 50 wt.% to 100 wt.% of the polymer matrix, about 70 wt.% to 100 wt.% in some embodiments, and about 90 wt.% to 100 wt.% (e.g., 100 wt.%) in some embodiments.

[0017] Polyarylene sulfides can be homopolymers or copolymers. For example, selective combinations of dihaloaromatic compounds can yield polyarylene sulfide copolymers containing at least two different units. For instance, when p-dichlorobenzene is used in combination with m-dichlorobenzene or 4,4'-dichlorodiphenyl sulfone, polyarylene sulfide copolymers containing segments having the following structure can be formed:

[0018]

[0019] And chain segments with the following structure:

[0020]

[0021] Or a chain segment with the following structure:

[0022] .

[0023] Polyaryl sulfides can be linear, semi-linear, branched, or crosslinked. Linear polyaryl sulfides typically contain 80 mol% or more of repeating units –(Ar–S)–. These linear polymers may also contain small amounts of branching or crosslinking units, but the amount of branching or crosslinking units is typically less than about 1 mol% of the total monomer units of the polyaryl sulfide. Linear polyaryl sulfide polymers can be random copolymers or block copolymers containing the aforementioned repeating units. Semi-linear polyaryl sulfides can also have crosslinked or branched structures formed by introducing small amounts of one or more monomers having three or more reactive functional groups into the polymer. By way of example, the monomeric component used to form a semi-linear polyaryl sulfide may include a certain amount of a polyhalogenated aromatic compound having two or more halogenated substituents per molecule, which can be used to prepare branched polymers. Such monomers can be derived from the formula R'X. n The expression indicates that each X is selected from chlorine, bromine, and iodine, n is an integer from 3 to 6, R' is a polyvalent aromatic group with a valence of n, which may have up to about 4 methyl substituents, and the total number of carbon atoms in R' is in the range of 6 to about 16. Examples of polyhalogenated aromatic compounds having more than two halogen substituents per molecule that can be used to form semi-linear polyarylene sulfides include 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, 1,3-dichloro-5-bromobenzene, 1,2,4-triiodobenzene, 1,2,3,5-tetrabromobenzene, hexachlorobenzene, 1,3,5-trichloro-2,4,6-trimethylbenzene, 2,2',4,4'-tetrachlorobiphenyl, 2,2',5,5'-tetraiodobiphenyl, 2,2',6,6'-tetrabromo-3,3',5,5'-tetramethylbiphenyl, 1,2,3,4-tetrachloronaphthalene, 1,2,4-tribromo-6-methylnaphthalene, and mixtures thereof.

[0024] If desired, polyarylene sulfides can be functionalized. For example, disulfide compounds containing reactive functional groups (e.g., carboxyl, hydroxyl, amine, etc.) can react with polyarylene sulfides. Functionalization of polyarylene sulfides can also provide bonding sites between any impact modifier and the polyarylene sulfide, which can improve the distribution of the impact modifier throughout the polyarylene sulfide and prevent phase separation. The disulfide compound can undergo chain scission reactions with the polyarylene sulfide during melt processing to reduce its overall melt viscosity. When used, the disulfide compound typically constitutes about 0.01 wt.% to about 3 wt.% of the polymer composition, in some embodiments about 0.02 wt.% to about 1 wt.%, and in some embodiments about 0.05 wt.% to about 0.5 wt.%. The ratio of the amount of polyarylene sulfide to the amount of disulfide can also be from about 1000:1 to about 10:1, from about 500:1 to about 20:1, or from about 400:1 to about 30:1. Suitable disulfide compounds are typically those having the following formula:

[0025] R 3 –S–S–R 4

[0026] Where R 3 and R 4 They can be the same or different, and are independently composed of hydrocarbon groups of 1 to 20 carbons. For example, R 3 and R 4 It can be alkyl, cycloalkyl, aryl, or heterocyclic. In some embodiments, R 3 and R 4 These are generally non-reactive functional groups, such as phenyl, naphthyl, ethyl, methyl, and propyl. Examples of these compounds include diphenyl disulfide, naphthyl disulfide, dimethyl disulfide, diethyl disulfide, and dipropyl disulfide. 3 and R 4 It may also include reactive functional groups at one or more ends of the disulfide compound. For example, R 3 and R 4At least one of them may include a terminal carboxyl group, a hydroxyl group, a substituted or unsubstituted amino group, a nitro group, etc. Examples of compounds may include, but are not limited to, 2,2'-diaminodiphenyl disulfide, 3,3'-diaminodiphenyl disulfide, 4,4'-diaminodiphenyl disulfide, dibenzyl disulfide, dithiosalicylic acid (or 2,2'-dithiobenzoic acid), dithioglycolic acid, α,α'-dithiodilactate, β,β'-dithiodilactate, 3,3'-dithiodipyridine, 4,4'-dithiomorpholine, 2,2'-dithiobis(benzothiazole), 2,2'-dithiobis(benzimidazole), 2,2'-dithiobis(benzoxazole), 2-(4'-morpholinodithio)benzothiazole, etc., and mixtures thereof.

[0027] The melt flow rate of polyarylene sulfides can be from about 100 g / 10 min to about 800 g / 10 min (“g / 10 min”), in some embodiments from about 200 g / 10 min to about 700 g / 10 min, and in some embodiments from about 300 g / 10 min to about 600 g / 10 min, as determined according to ISO 1133-1:2022 at a load of 5 kg and a temperature of 316 °C.

[0028] The typical DTUL values ​​of polyarylene sulfides described above are from about 70°C to about 220°C, in some embodiments from about 90°C to about 200°C, and in some embodiments from about 120°C to about 180°C, as determined according to ISO 75-2:2013 under a load of 1.8 MPa. Polyarylene sulfides also typically have glass transition temperatures from about 50°C to about 120°C, in some embodiments from about 60°C to about 115°C, and in some embodiments from about 70°C to about 110°C, and melting temperatures from about 220°C to about 340°C, in some embodiments from about 240°C to about 320°C, and in some embodiments from about 260°C to about 300°C.

[0029] B. Inorganic fibers

[0030] As described above, inorganic fibers are also employed in the polymer composition, which can simultaneously improve the crystallization rate of the composition as well as its thermal and mechanical properties. Inorganic fibers typically exhibit high tensile strength relative to their mass. For example, the ultimate tensile strength of the fiber (determined according to ASTM D822 / D822M-13 (2018)) is typically from about 1,000 MPa to about 15,000 MPa, in some embodiments from about 2,000 MPa to about 10,000 MPa, and in some embodiments from about 3,000 MPa to about 6,000 MPa. Furthermore, although the fibers can have a variety of different sizes, fibers with specific sizes can contribute to improved mechanical properties of the resulting polymer composition. The nominal diameter of the inorganic fiber can be, for example, from about 5 micrometers to about 40 micrometers, in some embodiments from about 6 micrometers to about 30 micrometers, in some embodiments from about 8 micrometers to about 20 micrometers, and in some embodiments from about 9 micrometers to about 15 micrometers. The fibers (after blending) can also have a relatively high aspect ratio (average length (μm) divided by nominal diameter (μm)), for example, about 2 or greater, about 4 to about 100 in some embodiments, about 5 to about 50 in some embodiments, and about 8 to about 40 is particularly advantageous in some embodiments. The volume average length (after blending) of such fibers can, for example, be about 10 micrometers or greater, about 25 micrometers or greater in some embodiments, about 50 micrometers or greater to about 800 micrometers or less in some embodiments, and about 60 micrometers to about 500 micrometers in some embodiments. The relative amount of fibers can also be selectively controlled to help achieve a desired crystallization rate without adversely affecting other properties of the composition, such as its flowability and mechanical properties. For example, inorganic fibers can constitute about 30 to about 120 parts by weight per 100 parts by weight of polymer matrix, about 40 to about 110 parts by weight in some embodiments, and about 50 to about 100 parts by weight in some embodiments. For example, inorganic fibers may constitute about 20 wt.% to about 60 wt.% of the polymer composition, about 25 wt.% to about 55 wt.% in some embodiments, and about 30 wt.% to about 50 wt.% in some embodiments.

[0031] In addition to size, strength, and relative concentration, the composition of inorganic fibers can also be selectively controlled to achieve a better crystallization rate. Generally, inorganic fibers can be formed from inherently insulating materials such as glass, ceramics (e.g., alumina or silica), etc. Glass fibers are particularly suitable, such as E-glass, E-CR glass, A-glass, C-glass, D-glass, AR-glass, R-glass, S1-glass, S2-glass, etc., and mixtures of any of the foregoing. Generally boron-free glass fibers (e.g., E-CR glass fibers) are particularly suitable. In some embodiments, the glass fibers may contain silica (SiO2), alumina (Al2O3), and oxides of calcium and magnesium (e.g., CaO, MgO, etc.), but generally do not contain boron and optional fluorides. For example, the glass fibers may contain boron at a concentration of about 1 wt.% or less relative to the total weight of the glass fibers, in some embodiments about 0.5 wt.% or less, and in some embodiments about 0.1 wt.% or less (e.g., 0 wt.%). The glass fiber may also contain fluoride at a concentration of about 0.5 wt.% or less relative to the total weight of the glass fiber, in some embodiments about 0.2 wt.% or less, and in some embodiments about 0.01 wt.% or less (e.g., 0 wt.%). The boron concentration and fluoride concentration can be measured by inductively coupled plasma atomic emission spectrometry. In the absence of boron oxide, the glass fiber may also contain titanium dioxide (TiO2) to reduce melt viscosity. For example, the concentration of titanium in the glass fiber may be from about 0.1 wt.% to about 1 wt.% of the total weight of the glass fiber, and in some embodiments from about 0.15 wt.% to about 0.5 wt.%. In addition to titanium dioxide, the glass fiber may also contain potassium oxide (K2O) and / or lithium oxide (Li2O) as fluxing agents. For example, the concentration of potassium in the glass fiber may be from about 0.2 wt.% to about 1 wt.% of the total weight of the glass fiber, and in some embodiments from about 0.3 wt.% to about 0.5 wt.%. The lithium concentration in the glass fiber can also be from about 0.1 wt.% to about 1 wt.% of the total weight of the glass fiber, and in some embodiments from about 0.2 wt.% to about 0.5 wt.%. The glass fiber can also have a relatively low content of sodium oxide (Na₂O). For example, the sodium concentration in the glass fiber can be from about 0.1 wt.% to about 1 wt.% of the total weight of the glass fiber, and in some embodiments from about 0.2 wt.% to about 0.5 wt.%. The concentrations of titanium, potassium, lithium, and sodium can be measured by ICP-AES.In one particular embodiment, the glass fiber may contain about 57.5 wt.% to about 59.5 wt.% of silicon dioxide, about 17 wt.% to about 20 wt.% of aluminum oxide, about 11 wt.% to about 13.5 wt.% of calcium oxide, about 8.5 wt.% to about 12.5 wt.% of magnesium oxide, and optionally sodium oxide, potassium oxide, lithium oxide and / or titanium oxide. Other oxides, such as iron oxide (Fe2O3), may also be used.

[0032] If desired, inorganic fibers may contain a sizing composition coated thereon to help improve the crystallization rate. The sizing composition may contain an organosilane compound capable of forming Si-O-Si covalent bonds between the glass fiber surface and silanols obtained through the hydrolysis of the silane compound, and between adjacent silanol groups. The resulting covalent bonds form a cross-linked structure at the fiber surface, which can enhance hydrolysis resistance. Such organosilane compounds may, for example, constitute from about 2 wt.% to about 40 wt.% of the solids content (i.e., excluding water) of the sizing composition, from about 2.5 wt.% to about 20 wt.% in some embodiments, and from about 5 wt.% to about 15 wt.% in some embodiments. The organosilane compound may be, for example, any alkoxysilane known in the art, such as vinylalkoxysilanes, epoxyalkoxysilanes, aminoalkoxysilanes, mercaptoalkoxysilanes, and combinations thereof. In one embodiment, for example, the organosilane compound may have the following general formula:

[0033] R 5 -Si-(R 6 )3,

[0034] in,

[0035] R 5 These include sulfide groups (e.g., -SH), alkyl sulfides containing 1 to 10 carbon atoms (e.g., mercaptopropyl, mercaptoethyl, mercaptobutyl, etc.), alkenyl sulfides containing 2 to 10 carbon atoms, alkynyl sulfides containing 2 to 10 carbon atoms, amino groups (e.g., NH2), aminoalkyl groups containing 1 to 10 carbon atoms (e.g., aminomethyl, aminoethyl, aminopropyl, aminobutyl, etc.); aminoalkenyl groups containing 2 to 10 carbon atoms, aminoalkynyl groups containing 2 to 10 carbon atoms, and so on.

[0036] R 6 It is an alkoxy group with 1 to 10 carbon atoms, such as methoxy, ethoxy, propoxy, etc.

[0037] Aminosilane compounds are particularly suitable and may comprise monomeric or oligomeric (<6 units) silanes. In some embodiments, aminotrialkoxysilanes may be used to form a three-dimensional network of Si-O-Si covalent bonds on and around the surface of the fiber. In some embodiments, aminodialkoxysilanes may also be used to form a hair-like structure on the surface of the fiber. While dialkoxysilanes do not necessarily form a three-dimensional cross-linked protective sheath around the fiber, they can still facilitate the impregnation of the fiber bundle and the wetting of individual fibers by the polymer melt, as well as reduce the hydrophilicity of the fiber surface, which is considered to contribute to hydrolysis resistance. Therefore, the use of trialkoxysilanes, dialkoxysilanes, or mixtures thereof in the sizing composition is desirable. Suitable examples of aminosilanes may include, for instance, aminodiakoxysilanes, such as γ-aminopropylmethyldiethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminoisobutylmethyldimethoxysilane, γ-aminopropylmethyldimethoxysilane, N-β-(aminoethyl)-γ-aminopropylmethyldiethoxysilane, etc.; aminotrialkoxysilanes, such as γ-... -Aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltriethoxysilane, diethylenetriaminopropyltrimethoxysilane, bis-(γ-trimethoxysilylpropyl)amine, N-phenyl-γ-aminopropyltrimethoxysilane, γ-amino-3,3-dimethylbutyltrimethoxysilane, γ-aminobutyltriethoxysilane, etc.; and mixtures of any of the foregoing substances.

[0038] In addition to organosilane compounds, the sizing composition may also contain one or more functionalized compounds capable of crosslinking to form a three-dimensional polymer network. Where it is not desired to be limited by theory, this is believed to also enhance the fiber's ability to improve the composition's crystallization rate. When used, such functionalized compounds may constitute about 5 wt.% to about 90 wt.% of the solids content (i.e., excluding water) of the sizing composition, in some embodiments about 10 wt.% to about 80 wt.%, and in some embodiments about 15 wt.% to about 70 wt.%. In one embodiment, for example, the functionalized compound may be a capped isocyanate. As used herein, the term "capped isocyanate" refers to an isocyanate in which one or more isocyanate groups of an organic polyisocyanate have reversibly reacted with a capping agent. In this way, the resulting capped (partial or complete) isocyanate groups are stable to active hydrogen at ambient temperature, but can be decapsulated at elevated temperatures, making them reactive with active hydrogen, for example at temperatures between about 90°C and about 210°C, between about 105°C and about 180°C in some embodiments, and between about 125°C and about 170°C in some embodiments. Representative examples of suitable organic polyisocyanates include aliphatic isocyanates (e.g., trimethylene diisocyanate, tetramethylene diisocyanate, hexamethylene diisocyanate, butylene diisocyanate, etc.); (cyclo)aliphatic isocyanates (e.g., isophorone diisocyanate (IPDI), 4,4'-diisocyanate dicyclohexylmethane (HMDI), etc.); aromatic isocyanates (e.g., p-phenylene diisocyanate); aliphatic-aromatic isocyanates (e.g., 4,4'-diphenylmethane diisocyanate, 2,4- or 2,6-toluene diisocyanate, etc.); and mixtures thereof. Representative examples of suitable end-capping agents include, but are not limited to, oximes such as methyl ethyl ketone oxime, acetone oxime, and cyclohexanone oxime; lactams such as ε-caprolactam; alcohols; malonates; alkyl acetoacetates; triazoles; pyrazoles; phenols; amines such as benzyl tert-butylamine; and mixtures thereof. In one embodiment, the capped isocyanate is a capped alicyclic polyisocyanate.

[0039] The functionalized compound may also include polymers containing anhydride and / or carboxylic acid functional groups. Examples of such polymers may include copolymers of ethylene-maleic anhydride, butadiene-maleic anhydride, isobutylene-maleic anhydride, acrylate-maleic anhydride, polyacrylic acid, etc. When used, such anhydride and / or carboxylic acid functionalized polymers may constitute about 5 wt.% to about 60 wt.% of the solids content (i.e., excluding water) of the sizing composition, in some embodiments about 10 wt.% to about 40 wt.%, and in some embodiments about 15 wt.% to about 30 wt.%. Other functionalized polymers may also be used, either alone or in combination with polymers containing anhydride and / or carboxylic acid functional groups. In some embodiments, for example, epoxy-functionalized polymers may be used, such as epoxy phenolic varnish (EPN), epoxy cresol varnish (ECN), etc. When used, such epoxy-functionalized polymers can constitute about 30 wt.% to about 90 wt.% of the solids content (i.e., excluding water) of the sizing composition, about 40 wt.% to about 80 wt.% in some embodiments, and about 50 wt.% to about 70 wt.% in some embodiments. In some embodiments, combinations of such functionalized polymers may also be used. Indeed, it is believed that a dense cross-linked sheath can be formed around inorganic fibers through the reaction of epoxy groups with maleic anhydride and / or carboxylic acid groups.

[0040] In addition to organosilanes and functionalized compounds, the sizing composition may also contain a film-forming agent that helps protect the fibers from damage during processing and promotes fiber compatibility with the polymer matrix. Particularly suitable film-forming agents are polymers such as polyurethanes, (meth)acrylate polymers, epoxy resin emulsions (e.g., bisphenol A-based or bisphenol F-based epoxy), epoxy ester resins, epoxy urethane resins, polyamides, and mixtures of any of the foregoing. In a particular embodiment, for example, the film-forming agent may include a similarly functionalized polymer, such as a polymer containing isocyanate-terminated functional groups as described above. Examples of such functionalized film-forming agents may include polyester-based polyurethanes and polyether-based polyurethanes containing isocyanates. When used, such film-forming agents may constitute from about 0.1 wt.% to about 50 wt.% of the solids content (i.e., excluding water) of the sizing composition, from about 1 wt.% to about 40 wt.% in some embodiments, and from about 5 wt.% to about 30 wt.% in some embodiments. Other additives may also be used in the sizing composition, such as pH adjusters, lubricants, antistatic agents, defoamers, crosslinking agents, etc.

[0041] The sizing composition can be applied to the surface of inorganic fibers in various ways. For example, the sizing composition can be applied as the fibers are forming from a stencil. The entire composition can also be applied to the fibers in a single step, or one or more components of the sizing composition can be applied separately. For example, in one embodiment, a two-stage application process can be employed, wherein a polymer containing anhydride and / or carboxylic acid functional groups is applied in a first stage, and a polymer containing epoxy functional groups is applied in a second stage. In this way, the polymers can be crosslinked together only after being applied to the fiber surface. Other components of the sizing composition can be applied separately or in combination with one or two of the polymers. Regardless of the specific process used, one or more solvents (e.g., water) can be added to the components of the sizing composition during application to facilitate the coating process. Once coated, the fibers can be dried to remove the solvent. At this point, the moisture content of the coated fibers is typically about 0.5 wt.% or less, about 0.2 wt.% or less in some embodiments, and about 0.1 wt.% or less in some embodiments. Similarly, the amount of sizing composition used is typically from about 0.3 wt.% to about 1.2 wt.% based on the total weight of the coated fibers, from about 0.4 wt.% to about 1 wt.% in some embodiments, and from about 0.5 wt.% to about 0.8 wt.% in some embodiments.

[0042] C. Optional components

[0043] In addition to the components described above, the polymer composition may also contain a variety of other optional components to help improve its overall properties. If desired, for example, an organosilane compound may also be used in the polymer composition, for example, in an amount of about 0.1 parts by weight to about 8 parts by weight per 100 parts by weight of the polymer matrix, in some embodiments about about 0.3 parts by weight to about 5 parts by weight, and in some embodiments about about 0.5 parts by weight to about 3 parts by weight. For example, the organosilane compound may constitute about 0.01 wt.% to about 3 wt.% of the polymer composition, in some embodiments about about 0.05 wt.% to about 2 wt.%, and in some embodiments about about 0.1 wt.% to about 1 wt.%. The organosilane compound may be, for example, any alkoxysilane known in the art, such as vinylalkoxysilane, epoxyalkoxysilane, aminoalkoxysilane, mercaptoalkoxysilane, and combinations thereof. In one embodiment, for example, the organosilane compound may have the following general formula:

[0044] R 5 -Si-(R 6 )3,

[0045] in,

[0046] R5 This includes sulfide groups (e.g., -SH), alkyl sulfides containing 1 to 10 carbon atoms (e.g., mercaptopropyl, mercaptoethyl, mercaptobutyl, etc.), alkenyl sulfides containing 2 to 10 carbon atoms, alkynyl sulfides containing 2 to 10 carbon atoms, amino groups (e.g., NH2), aminoalkyl groups containing 1 to 10 carbon atoms (e.g., aminomethyl, aminoethyl, aminopropyl, aminobutyl, etc.); aminoalkenyl groups containing 2 to 10 carbon atoms, aminoalkynyl groups containing 2 to 10 carbon atoms, etc.; and...

[0047] R 6 It is an alkoxy group with 1 to 10 carbon atoms, such as methoxy, ethoxy, propoxy, etc.

[0048] Some representative examples of organosilane compounds that may be included in mixtures include mercaptopropyltrimethoxysilane, mercaptopropyltriethoxysilane, aminopropyltriethoxysilane, aminoethyltriethoxysilane, aminopropyltrimethoxysilane, aminoethyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, ethynyltrimethoxysilane, ethynyltriethoxysilane, aminoethylaminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropylmethyldimethoxysilane or 3-aminopropylmethyldiethoxysilane, N-(2-aminoethyl)-3-amino γ-aminopropyltrimethoxysilane, N-methyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, bis(3-aminopropyl)tetramethoxysilane, bis(3-aminopropyl)tetraethoxydisiloxane, γ-aminopropyltrimethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, N-phenyl-γ-aminopropyltrimethoxysilane, γ-diallylaminopropyltrimethoxysilane, γ-diallylaminopropyltrimethoxysilane, etc., and combinations thereof. Particularly suitable organosilane compounds are 3-aminopropyltriethoxysilane and 3-mercaptopropyltrimethoxysilane.

[0049] Impact modifiers may also be used in polymer compositions. When used, one or more impact modifiers typically constitute from about 1 to about 30 parts by weight of polyarylene sulfide per 100 parts by weight, in some embodiments from about 2 to about 20 parts by weight, and in some embodiments from about 5 to about 15 parts by weight. For example, the impact modifier may constitute from about 0.1 wt.% to about 20 wt.% of the polymer composition, in some embodiments from about 0.5 wt.% to about 15 wt.%, and in some embodiments from about 1 wt.% to about 10 wt.%.

[0050] Examples of suitable impact modifiers may include, for example, polyepoxides, polyurethanes, polybutadiene, acrylonitrile-butadiene-styrene, polyamides, block copolymers (e.g., polyether-polyamide block copolymers), and mixtures thereof. In one embodiment, an olefin copolymer is employed, which is "epoxy-functionalized" because it contains an average of two or more epoxy functional groups per molecule. The copolymer generally contains olefin monomer units derived from one or more α-olefins. Examples of such monomers include, for example, straight-chain and / or branched α-olefins having 2 to 20 carbon atoms, typically 2 to 8 carbon atoms. Specific examples include ethylene, propylene, 1-butene; 3-methyl-1-butene; 3,3-dimethyl-1-butene; 1-pentene; 1-pentene having one or more methyl, ethyl, or propyl substituents; 1-hexene having one or more methyl, ethyl, or propyl substituents; 1-heptene having one or more methyl, ethyl, or propyl substituents; 1-octene having one or more methyl, ethyl, or propyl substituents; 1-nonene having one or more methyl, ethyl, or propyl substituents; 1-decene substituted with ethyl, methyl, or dimethyl; 1-dodecene; and styrene. Particularly desirable α-olefin monomers are ethylene and propylene. The copolymer may also contain epoxy-functionalized monomer units. An example of such units is an epoxy-functionalized (meth)acrylic acid monomer component. As used herein, the term "(meth)acrylic acid" includes acrylic acid monomers and methacrylic acid monomers, as well as their salts or esters, such as acrylate monomers and methacrylate monomers. For example, suitable epoxy-functionalized (meth)acrylate monomers may include, but are not limited to, those containing 1,2-epoxy groups, such as glycidyl acrylate and glycidyl methacrylate. Other suitable epoxy-functionalized monomers include allyl glycidyl ether, ethyl glycidyl acrylate, and itaconic acid glycidyl ester. Other suitable monomers may also be used to help achieve the desired molecular weight.

[0051] Of course, the copolymer may also contain other monomer units known in the art. For example, another suitable monomer may include a non-epoxy-functional (meth)acrylic acid monomer. Examples of such (meth)acrylic acid monomers may include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, sec-butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-pentyl acrylate, isoamyl acrylate, isobornyl acrylate, n-hexyl acrylate, 2-ethylbutyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, n-decyl acrylate, methylcyclohexyl acrylate, cyclopentyl acrylate, cyclohexyl acrylate, methyl methacrylate, ethyl methacrylate, 2-hydroxyethyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isopropyl methacrylate, isobutyl methacrylate, n-pentyl methacrylate, n-hexyl methacrylate, isoamyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, 2-ethylbutyl methacrylate, methylcyclohexyl methacrylate, cinnamyl methacrylate, crotonyl methacrylate, cyclohexyl methacrylate, cyclopentyl methacrylate, 2-ethoxyethyl methacrylate, isobornyl methacrylate, etc., and combinations thereof. In one particular embodiment, for example, the copolymer may be a terpolymer formed from an epoxy-functional (meth)acrylic acid monomer component, an α-olefin monomer component, and a non-epoxy-functional (meth)acrylic acid monomer component. For example, the copolymer may be poly(ethylene-co-butyl acrylate-co-glycidyl methacrylate).

[0052] The relative proportions of the monomer components can be selected to achieve a balance between epoxy reactivity and melt flow rate. More specifically, a high epoxy monomer content can produce good reactivity with polyarylene sulfides, but an excessively high content can reduce the melt flow rate to a degree that adversely affects the melt strength of the polymer blend. Therefore, in most embodiments, epoxy-functionalized (meth)acrylate monomers constitute about 1 wt.% to about 20 wt.% of the copolymer, in some embodiments about 2 wt.% to about 15 wt.%, and in some embodiments about 3 wt.% to about 10 wt.%. Similarly, α-olefin monomers can constitute about 55 wt.% to about 95 wt.% of the copolymer, in some embodiments about 60 wt.% to about 90 wt.%, and in some embodiments about 65 wt.% to about 85 wt.%. When used, other monomeric components (e.g., non-epoxy-functional (meth)acrylic acid monomers) may constitute about 5 wt.% to about 35 wt.% of the copolymer, about 8 wt.% to about 30 wt.% in some embodiments, and about 10 wt.% to about 25 wt.% in some embodiments. The resulting melt flow rate is typically about 1 g / 10 min to about 30 g / 10 min (“g / 10 min”), about 2 g / 10 min to about 20 g / 10 min in some embodiments, and about 3 g / 10 min to about 15 g / 10 min in some embodiments, as measured according to ASTM D1238-13 at a load of 2.16 kg and a temperature of 190 °C.

[0053] Other components that may be included in the composition may include, for example, particulate fillers (e.g., talc, mica, etc.), pigments (e.g., black pigments), antioxidants, stabilizers (e.g., heat stabilizers, UV stabilizers, etc.), surfactants, waxes, flow promoters, lubricants, and other materials added to enhance performance and processability.

[0054] II. Melt processing

[0055] The combination of polyarylene sulfides, inorganic fibers, and various other optional additives can be varied as is known in the art. For example, materials can be supplied simultaneously or sequentially to a melt processing apparatus for dispersing blends. Batch and / or continuous melt processing technologies can be employed. For example, mixers / kneaders, Banbury mixers, Farrel continuous mixers, single-screw extruders, twin-screw extruders, roller mills, etc., can be used for blending and melt processing materials. A particularly suitable melt processing apparatus is a co-rotating twin-screw extruder (e.g., a Leistritz co-rotating fully meshing twin-screw extruder). Such extruders can include feed ports and vent ports and provide highly dispersive and cohesive mixing. For example, components can be fed into the same or different feed ports of a twin-screw extruder and melt-blended to form a substantially homogeneous melt mixture. Melt blending can be carried out under high shear / pressure and heating to ensure adequate dispersion. For example, melt processing can be performed at temperatures ranging from about 100°C to about 500°C, and in some embodiments, at temperatures ranging from about 150°C to about 300°C. Similarly, the apparent shear rate during melt processing can be about 100 seconds. -1 Approximately 10,000 seconds -1 Within that range, and in some implementations, in approximately 500 seconds -1 Approximately 1,500 seconds -1 Within a certain range. Of course, other variables, such as the residence time during melt processing (which is inversely proportional to the output rate), can also be controlled to achieve the desired homogeneity.

[0056] If desired, one or more distributive and / or dispersive mixing elements can be employed within the mixing section of the melt processing unit. Suitable distributive mixers may include, for example, Saxon, Dulmage, CavityTransfer mixers, etc. Similarly, suitable dispersive mixers may include Blister rings, Leroy / Maddock, CRD mixers, etc. As is known in the art, mixing intensity can be further enhanced by using pins in the barrel that cause the polymer melt to fold and reorient, such as those used in Buss kneader extruders, cavity transfer mixers, and Vortex intermeshing pin mixers. The screw speed can also be controlled to improve the properties of the composition. For example, the screw speed may be about 400 rpm or lower, in one embodiment, for example, between about 200 rpm and about 350 rpm, or between about 225 rpm and about 325 rpm. In one embodiment, compounding conditions can be balanced to provide a polymer composition exhibiting improved performance. For example, compounding conditions can include screw designs that provide mild, medium, or aggressive screw conditions. For instance, a system can have a mildly aggressive screw design where the screw has a single melting section in the downstream half, intended for gentle melting and distributed melt homogenization. A moderately aggressive screw design can have a stronger melting section upstream of the packing feed barrel, focusing more on stronger dispersing elements for homogeneous melting. Additionally, it can have another mild mixing section downstream to mix the packing. While weaker, this section can still increase the screw's shear strength, making it stronger overall than the mildly aggressive design. A highly aggressive screw design can have the strongest shear strength of the three. The main melting section can consist of a long row of highly dispersible kneaded blocks. The downstream mixing section can utilize the mixing of dispersing and strongly dispersing elements to achieve homogeneous dispersion of all types of packing. The shear strength of the highly aggressive screw design can be significantly higher than the other two designs. In one implementation, the system may include a moderate to aggressive screw design with a relatively mild screw speed (e.g., between about 200 rpm and about 300 rpm).

[0057] III. Molded parts

[0058] Various techniques can be used to form molded parts from polymer compositions. Suitable techniques may include, for example, injection molding, low-pressure injection molding, extrusion compression molding, gas injection molding, foam injection molding, low-pressure gas injection molding, low-pressure foam injection molding, gas extrusion compression molding, foam extrusion compression molding, extrusion molding, foam extrusion molding, compression molding, foam compression molding, gas compression molding, etc. For example, an injection molding system can be used, which includes a mold in which a polymer composition can be injected. The time inside the syringe can be controlled and optimized so that the polymer matrix does not pre-cur. When the cycle time is reached and the barrel is full and ready for discharge, the composition can be injected into the mold cavity using a plunger. Compression molding systems can also be used. As with injection molding, the molding of the polymer composition into the desired article also takes place within the mold. The composition can be placed into the compression mold using any known technique, such as by being picked up by an automated robotic arm. The temperature of the mold can be maintained at or above the solidification temperature of the polymer composition for a desired period of time to allow solidification. The molded product can then be cured by bringing its temperature below the melt temperature. The resulting product can be demolded. The cycle time for each molding process can be adjusted to suit the polymer composition, achieving full bonding and improving overall process productivity.

[0059] This polymer composition is particularly suitable for injection-molded parts with small dimensional tolerances. For example, as is known in the art, injection can occur in two main phases—the injection phase and the holding phase. During the injection phase, the mold cavity is completely filled with the molten polymer composition. The holding phase begins after the injection phase, during which the holding pressure is controlled to fill the mold cavity with additional material and to compensate for volume shrinkage that occurs during cooling. After injection, the part can be cooled. Once cooling is complete, the molding cycle is completed when the mold is opened and the part is ejected, for example with the aid of ejector pins within the mold.

[0060] Generally, any suitable injection molding equipment can be used. For example, refer to... Figure 1This illustration shows one embodiment of an injection molding apparatus or tool 10 that can be employed. In this embodiment, the apparatus 10 includes a first mold base 12 and a second mold base 14, which together define a mold cavity 16 defining an article or part. The molding apparatus 10 also includes a resin flow path extending from the outer surface 20 of the first half-mold 12 through a sprue 22 to the mold cavity 16. The resin flow path may also include runners and gates, neither of which are shown for simplicity. The polymer composition can be supplied to the resin flow path using a variety of techniques. For example, the polymer composition can be supplied (e.g., in granule form) to a feed hopper attached to an extruder barrel containing a rotating screw (not shown). As the screw rotates, the granules are moved forward and subjected to pressure and friction, which generates heat to melt the granules. Additional heat can also be provided to the composition via a heating medium in communication with the extruder barrel. One or more ejector pins 24 can also be employed, which are slidably fixed within the second half-mold 14 to define the mold cavity 16 in the closed position of the apparatus 10. Ejector pin 24 operates in a known manner to remove the molded part from the mold cavity 16 in the open position of the molding device 10.

[0061] A cooling mechanism can also be provided to cure the resin within the mold cavity. Figure 1 For example, each of mold bases 12 and 14 includes one or more cooling lines 18 through which a cooling medium flows to impart a desired mold temperature to the surface of the mold base, thereby solidifying the molten material. Due to the unique crystallinity of the polymer composition, the “cooling time” during the molding cycle can be significantly reduced while still achieving the same degree of crystallinity. The cooling time can be expressed as a “normalized cooling ratio,” which is determined by dividing the total cooling time by the average thickness of the molded part. As a result of the invention, the normalized cooling ratio can range from about 0.2 s / mm to about 8 s / mm, in some embodiments from about 0.5 s / mm to about 6 s / mm, and in some embodiments from about 1 s / mm to about 5 s / mm. The total cooling time can be determined from the point in time when the composition is injected into the mold cavity to the point in time when it reaches an ejection temperature that allows for safe ejection. Exemplary cooling times can range from, for example, about 1 second to about 60 seconds, in some embodiments from about 5 seconds to about 40 seconds, and in some embodiments from about 10 seconds to about 35 seconds.

[0062] In addition to minimizing the cooling time required for the molding cycle, the methods and compositions of the present invention also allow for molding parts at lower temperatures while still achieving the same degree of crystallinity. For example, the mold temperature (e.g., the temperature of the mold surface) can be from about 50°C to about 120°C, in some embodiments from about 60°C to about 110°C, and in some embodiments from about 70°C to about 90°C. Besides minimizing the energy requirements of the molding operation, such low mold temperatures can be achieved using cooling media that are less corrosive and less expensive than some conventional techniques. For example, liquid water can be used as the cooling medium.

[0063] Regardless of the molding technology used, polymer compositions can be molded into parts for any application, such as electric vehicles, fuel cell or alkaline electrolyzer systems, battery assemblies, electronic components, etc. Examples of electronic components may include, for example, cellular phones, laptop computers, small portable computers (e.g., ultra-portable computers, netbooks, and tablets), wristwatches, pendant devices, headphones and earphones, media players with wireless communication capabilities, handheld computers (sometimes also called personal digital assistants), remote controls, global positioning system (GPS) devices, handheld gaming devices, battery covers, speakers, camera modules, integrated circuits (e.g., SIM cards), etc.

[0064] In one particular embodiment, the polymer composition described herein can be incorporated into various components of an electric vehicle, such as battery systems (e.g., busbars, housings, etc.), electrical systems (e.g., inverter modules), interconnection systems (e.g., connectors, EMI cores, etc.), thermal management systems, etc. For example, the thermal management system of an electric vehicle can generally include multiple different subsystems, such as, but not limited to, powertrain subsystems, refrigeration subsystems, battery cooling subsystems, and heating, ventilation, and cooling (HVAC) subsystems. In some embodiments, one or more subsystems of the thermal management system can be fluidly connected to each other, thereby allowing a hotter heat transfer medium to flow from a high-temperature loop to a low-temperature loop, and allowing a colder heat transfer medium to flow from a low-temperature loop to a high-temperature loop. By way of example, a first temperature control loop in a typical electric vehicle can include a heat transfer medium (e.g., water, coolant, or a mixture thereof) pumped through the loop via a suitable pump (e.g., an electric pump) and cooled by heat exchange with a refrigerant in a heat exchanger (e.g., an energy storage system (ESS) heat exchanger) and by a radiator / reservoir. Furthermore, the circuit may include a heater (e.g., a positive temperature coefficient (PTC) heater) that ensures the system temperature is maintained within its preferred operating range regardless of ambient temperature, and the battery assembly. The second temperature control circuit may also include a heat transfer medium, which may be the same as or different from the heat transfer medium of another subsystem. The heat transfer medium of the second temperature control circuit can be pumped through the circuit using a suitable pump, heat exchanger, and radiator reservoir. The high-temperature control circuit can be used to cool the vehicle's power electronics and motors. In one particular embodiment, the polymer composition can be used in an electric coolant pump, which may include an electric motor as a drive source and hydraulic components for generating coolant suction and discharge forces. The electric motor and associated components are housed within an electric motor housing. Various components of the electric pump, such as housings, enclosures, interfaces, etc., may contain the polymer composition of the present invention.

[0065] The present invention can be better understood by referring to the following embodiments.

[0066] Test methods

[0067] Melt viscosity: Melt viscosity (Pa-s) can be determined according to ISO 11443:2021 at 400s. -1The shear rate was measured using a Dynisco LCR7001 capillary rheometer. The rheometer orifice (dial) diameter was 1 mm, the length was 20 mm, the L / D ratio was 20.1, and the inlet angle was 180°. The barrel diameter was 9.55 mm ± 0.005 mm, and the plunger rod length was 233.4 mm. Melt viscosity was typically measured at 310°C.

[0068] Tensile modulus, tensile stress at break, and tensile strain at break: Tensile properties can be tested according to ISO 527-2 / 1A:2019 (technically equivalent to ASTM D638-14). Modulus and strength measurements can be performed on the same test strip sample, which is 80 mm long, 10 mm thick, and 4 mm wide. The test temperature can be 23°C, and the test speed can be 5 mm / min.

[0069] Flexural modulus and flexural stress: Flexural properties can be tested according to ISO 178:2019 (technically equivalent to ASTM D790-10). This test can be performed over a support span of 64 mm. The test can be performed on the center portion of an uncut ISO 3167 multipurpose bar. The test temperature can be 23°C, and the test speed can be 2 mm / min.

[0070] Simply supported beam impact strength: The performance of simply supported beams can be tested according to ISO 179-1:2010 (technically equivalent to ASTM D256-10, Method B). This test can be performed using a Type 1 specimen (80 mm in length, 10 mm in width, and 4 mm in thickness). The test can be performed with or without a notch. When testing notched impact strength, the notch can be a Type A notch (0.25 mm bottom radius). The specimen can be cut from the center of a multi-purpose bar using a single-tooth milling machine. The test temperature can be 23°C or -30°C.

[0071] Surface resistivity: Surface resistivity values ​​are generally determined according to IEC 62631-3-2-2016 (equivalent to ASTM D257-14). According to this procedure, a standard specimen (e.g., a 1-meter cube) is placed between two electrodes. A voltage is applied for sixty (60) seconds and the resistance is measured. Surface resistivity is the quotient of the potential gradient (in V / m) and the current per unit electrode length (in A / m), and generally represents the leakage current resistance along the surface of the insulating material. Since the four (4) endpoints of the electrodes define a square, the lengths in the quotient are canceled out, and surface resistivity is reported in ohms, although the more descriptive unit ohms / square is also frequently seen.

[0072] Comparative Examples 1 to 6

[0073] Comparative Examples 1 and 2 were melt-blended using a 32 mm Coperion co-rotating, fully intermeshing, twin-screw extruder and contained various concentrations of polyarylene sulfides (PPS-1, PPS-2, and PPS-3), glass fibers, silane coupling agents, nucleating agents, black pigment masterbatches, and a gycolube. The melt viscosity of PPS-1 was approximately 5.5 kpoise, and the melt flow rates of PPS-2 and PPS-3 were each approximately 500 g / 10 min (316°C, 5 kg). The glass fibers were E-glass fibers with a diameter of 10 micrometers.

[0074]

[0075] Once formed, the resulting composition is then injection molded and various properties are tested as described above. The results are shown below.

[0076]

[0077] Examples 1 to 7

[0078] Examples 1 through 7 were melt-mixed using a 32 mm Coperion co-rotating, fully intermeshing twin-screw extruder and contained various concentrations of polyarylene sulfides (PPS-1, PPS-2, and PPS-3), glass fibers, silane coupling agents, nucleating agents, and a lubricant (Glycolube). The glass fibers were E-CR glass fibers purchased from 3B under the designation "DS 8800-11P" (average fiber diameter 11 μm).

[0079]

[0080] Once formed, the resulting composition is then injection molded and various properties are tested as described above. The results are shown below.

[0081]

[0082] These and other modifications and variations of the invention can be practiced by those skilled in the art without departing from the spirit and scope of the invention. Furthermore, it should be understood that aspects of the various embodiments can be interchanged, in whole or in part. Moreover, those skilled in the art will understand that the foregoing description is merely exemplary and is not intended to limit the scope of the invention further described in the appended claims.

Claims

1. A polymer composition comprising 100 parts by weight of a polymer matrix containing polyarylene sulfides and about 30 parts by weight to about 120 parts by weight of inorganic fibers, wherein the polymer composition exhibits a peak crystallization temperature of about 230°C or higher as determined by differential scanning calorimetry according to ISO 11357-3:2018. p,c (and approximately 1.8% or higher tensile elongation as determined at 23°C according to ISO 527:2019).

2. The polymer composition of claim 1, wherein the polymer matrix constitutes about 30 wt.% to about 80 wt.% of the polymer composition.

3. The polymer composition according to claim 1, wherein the polyarylene sulfide is a polyphenylene sulfide.

4. The polymer composition according to claim 1, wherein the melt flow rate of the polyarylene sulfide is about 200 g / 10 min to about 700 g / 10 min, as determined according to ISO 1133-1:2022 at a load of 5 kg and a temperature of 316 °C.

5. The polymer composition according to claim 1, wherein the inorganic fiber comprises glass fiber.

6. The polymer composition according to claim 5, wherein the glass fiber is generally boron-free.

7. The polymer composition according to claim 5, wherein the glass fiber is E-CR glass fiber.

8. The polymer composition according to claim 5, wherein the glass fiber contains about 57.5 wt.% to about 59.5 wt.% of silicon dioxide, about 17 wt.% to about 20 wt.% of aluminum oxide, about 11 wt.% to about 13.5 wt.% of calcium oxide, and about 8.5 wt.% to about 12.5 wt.% of magnesium oxide.

9. The polymer composition according to claim 1, wherein the inorganic fibers are coated with a sizing composition.

10. The polymer composition according to claim 9, wherein the sizing composition contains an alkoxysilane.

11. The polymer composition according to claim 9, wherein the sizing composition contains a functionalized compound.

12. The polymer composition of claim 11, wherein the functionalized compound comprises a capped isocyanate.

13. The polymer composition of claim 12, wherein the end-capped isocyanate is decapped at a temperature of about 90°C to about 210°C.

14. The polymer composition of claim 12, wherein the terminated isocyanate comprises a terminated alicyclic polyisocyanate.

15. The polymer composition according to claim 9, wherein the sizing composition contains a film-forming agent.

16. The polymer composition of claim 9, wherein the moisture content of the coated inorganic fibers is about 0.5 wt.% or less.

17. The polymer composition according to claim 1, further comprising about 0.1 parts by weight to about 8 parts by weight of an organosilane compound.

18. The polymer composition according to claim 1, wherein the polymer composition exhibits a temperature of about 310°C and a s2 of 1,200 s according to ISO 11443:2021. -1 The melt viscosity was approximately 5,000 poise or lower, determined at a shear rate.

19. The polymer composition according to claim 1, wherein the composition is free of boron nucleating agents.

20. A molded part comprising the polymer composition of claim 1.